Feeling-living-fighting the housing crisis: testimonio as methodology in geographic housing research - Keller, Judith (Social & cultural geography, 2024)
While advocates and urbanites regard the housing crisis as a major challenge, federal and city officials seldom act with the urgency demanded of them by their constituency, of which a growing number is either unhoused or housing insecure. The aim of this paper is to study this crisis from the perspective of those most affected and contribute to a debate mostly dominated by economic and policy-oriented approaches. My use of testimonios collected in Washington, DC, between 2019 and 2022 reworks how knowledge on the housing crisis is constituted and highlights both the relational and collective knowledge production by those most affected by changes in the real estate economy. The goal of this paper is to stress the political potential and agency of people who tell their stories as they fight to (re)claim lost and threatened places and battle to protect their homes and neighbourhoods. On a broader scope, this paper sees value in everyday experiential knowledge and questions whose narratives of place are valued, in an effort to bring forth a new methodology in geographic housing research.